THE TEACHER'S FEEDBACK TECHNIQUE IN TEACHING DESCRIPTIVE TEXT AT THE SECOND YEAR OF SMP N 1 SRAGEN - Ismayanindar, Nimas, Mauly Halwat Hikmat, Ph. D, Nur Hidayat, M.Pd (2015)
This study is aimed at describing: 1) the teacher feedback technique used in teaching descriptive text, 2) the student's response of the teaching writing descriptive text, and 3) the problems faced by the teacher in teaching writing descriptive text. In achieving the objectives, the researcher used descriptive qualitative approach to collect and analyze the data. The research was held in SMP N 1 Sragen. The research took 32 students of the second year students as the subject of the study. The writer gets the data of the research from event ,informant, and document. The method of collecting data are the observation and interview about the writing teaching- learning process. The result of the analysis shows that teacher's corrective feedback techniques is appropriate and effective for the second year student of SMP N 1 Sragen in teaching descriptive text. By using this technique, the students are capable of knowing their errors, the reason and correct them. So, it can accelerate the teaching- learning writing process. They are interested, enthusiastic, and motivated to take part in the classroom activities. They are not bored and more entertained in the classroom, because the teacher also provided a picture and real object to be described as the medium of teaching. The teacher has several problems in teaching namely difficulty in explaining the content of the text, students' difficulties in developing paragraph in descriptive text, students' difficulties in mastering component of writing, and lacking of media.